Arup: CEGB - Maccormac, Richard
Nota crítica y desarrollo de las oficinas de CEGB en Bristol de Arup Associates .
Keywords: ARUP; ARUP, OVE NYQUIST; REINO UNIDO; INGLATERRA; BRISTOL; EDIFICIOS DE OFICINAS